Analisis Determinan Perataan Laba : Pendekatan Indeks Eckel - Sugi Suhartono; Vika Hendraswari (Jurnal Akuntansi dan Pajak, 2020)
Profit is an important thing for the survival of the company. Investors often only pay attention to profits without regard to the procedures used to generate earnings information. Income smoothing is a tool to minimize the fluctuations in earnings that will be reported and more to cover the information that should be disclosed. This study aims to examine the effect of return on assets, net profit margins, financial leverage, company size, and cash holding on income smoothing practices in manufacturing companies listed on the Indonesia Stock Exchange in the period 2016-2018. The sample of this research is manufacturing companies listed on Indonesia Stock Exchange during the 2016-2018 period. The total sample used was 69 companies with observational data obtained as many as 207 samples over three years. The sampling technique used was non-probability sampling using a purposive sampling method and the analysis technique used was logistic regression analysis with the help of SPSS 22.0 software. The conclusion of this study is that return on assets and firm size negatively affect the income smoothing practices, net profit margins have a positive effect on income smoothing practices, financial leverage and cash holding have no effect on income smoothing practices.